Trade reforms & the transmission effects : an analysis of the Guyanese experience - Thomas, Clive Y. (2007)
Provides quantitative and qualitative estimates of the effects on the Guyanese economy, agricultural sector and households from the implementation of trade reforms that begun in the late 1980s. Describes the period prior to the reforms and examines the rationale for what followed. Analyzes the reform period and its impact on the domestic economy. Provides a number of conclusions and recommendations for the way forward.